Resale Price Maintenance After Leegin: Why Treating Vertical Price-Fixing As “Inherently Suspect” Is the Only Viable Alternative to the Traditional Rule of Reason - John Austin Moore (Washington University Journal of Law & Policy, 2011)
The Article focuses on resale price maintenance (RPM) and price fixing in the U.S. Information is provided on the U.S. Supreme Court case Leegin Creative Leather Products Inc. v. PSKS Inc. which made vertical RPM legal under U.S. commerce law. Topics include the Court's interpretation of the U.S. Sherman Act and the validity of the rule of reason standard regarding price maintenance.
Keywords: Price regulation; Price maintenance -- Law & legislation; Price fixing; Leegin Creative Leather Products Inc. v. PSKS Inc. (Supreme Court case); United States. Sherman Act; United States. Supreme Court